Biometry in Umbu fruits from the semi-arid region of Paraiba - Fábio Rodrigo Araújo Pereira; Walter Esfrain Pereira; Angela Maria dos Santos Pessoa; Erika Socorro Alves Graciano de Vasconcelos (Revista Brasileira de Fruticultura, 2021)
Abstract Umbu fruits from four municipalities of Paraíba were morphologically characterized in order to identify promising genotypes for fresh consumption and agro-industrial use. We used 400 fruits from parent plants located in São Vicente do Seridó, Queimadas, Boqueirão, and Cabaceiras and 40 commercial fruits from two open fairs in Campina Grande, PB. The experimental unit consisted of ten fruits. The fruits were analyzed for total mass (MTF), length (LC), diameter (DF), fresh matter (MMF), yield (RF), and presence of hairs. In the endocarps, mass (ME), length (CE), diameter (DE), and width (LE) were the evaluated parameters. A completely randomized design was adopted, the data were subjected to variance analysis, and the means were compared by the Tukey test and principal component analysis. The fruits from Queimadas and São Vicente do Seridó showed the best morphological characters with regard to mass, length, diameter, fresh matter, and fruit yield, and were the most promising for agro-industrial commercialization. The fruits from Boqueirão showed the highest endocarp mass. Most fruits showed hairs on the peel, except the commercial ones. Four groups of municipalities were formed, with the fruits from Queimadas showing the largest size, while the fruits from São Vicente de Seridó and Soledade showed the highest yield.